Bone Marrow Fibrosis in Chronic myeloid leukemia (CML) and other Myeloproliferative Disorders Evaluated by Using Special Histochemical Stains for Collagen. - Al-Khafaji, Ali Khalil I.; Jaleel Al-Shammari, Haider H.; Hamudi Al-Obeidi, Salim R. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: It is still difficult to give a final diagnosis in chronic myeloproliferative disorders (CMPDs) because of the overlap of the common pathological and clinical features of these disorders like bone marrow fibrosis which is considered important because it affects the normal function of the bone marrow. The collagen fibers are of different types, but in the bone marrow, the two main types are: collagen I, which is the most abundant type and collagen III (reticular) which is often associated with type I.Objectives:To study bone marrow fibrosis (BMF) in samples of bone marrow biopsies (BMB) of chronic myeloid leukemia (CML) and other chronic myeloproliferative disorders using histochemical stains to establish the grade of fibrosis and enabling a correct differentiation between chronic myeloid leukemia, essential thrombocythemia (ET), polycythemia rubra vera (PRV), and idiopathic marrow fibrosis (IMF) as subtypes of myeloproliferative disorders.Patients and methods: This retrospective study included collection of previously preserved formalin fixed- paraffin embedded bone marrow trephine biopsies of patients with chronic myeloproliferative disorders from January 2003 through December 2008 .The relevant clinical data of patients were retrieved from the stored case sheets. Applied histochemical stains (Reticulin stain, Van Gieson stain, and trichrome stain) with Haematoxylin and Eosin (H&E) stain on sections from these specimens. These stains were used to detect the presence and the degree of pathological marrow fibrosis by the most recent grading system, the European Consensus 2005(EC2005) originally described by Thiele at 2003. Using Trichrome stain for collagen type I and reticulin stain for reticulin fibers (collagen type III) and by using a special marrow fibrosis grading system as a routine work with H&E is valuable in determining the degree of marrow fibrosis on bone marrow biopsy examination and simplifies the diagnosis.Results: Sixty eight percent of chronic myeloproliferative disorders patients had no marrow fibrosis when diagnosed by H&E, while only 30% of chronic myeloproliferative disorders patients had no marrow fibrosis when the diagnosis was made by special stains and marrow fibrosis grading system. There is rare marrow fibrosis in essential thrombocythemia, polycythemia rubra vera, but present in chronic myeloid leukemia and almost always in marrow fibrosis. Some patients really have myelofibrosis of different grades and the histological findings by using histochemical stains are crucial to distinguish between myeloproliferative diseasesConclusion: Patients with chronic myeloid leukemia and other chronic myeloproliferative disorders had marrow fibrosis of different grades, which is confirmed by using histochemical stains for different collagen fibers and special grading system for marrow fibrosis (EC2005) that has to be applied. It can be used routinely to avoid misdiagnosis of the primary disease or its conversion and transition to another chronic myeloproliferative disorders type, in which the clinical and laboratory features overlap, but the prognosis and therapeutic implications are significantly different.